2018
DOI: 10.1074/jbc.m117.808584
|View full text |Cite
|
Sign up to set email alerts
|

ST6Gal-I sialyltransferase promotes chemoresistance in pancreatic ductal adenocarcinoma by abrogating gemcitabine-mediated DNA damage

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignancy with a poor prognosis. Gemcitabine, as a single agent or in combination therapy, remains the frontline chemotherapy despite its limited efficacy due to or acquired chemoresistance. There is an acute need to decipher mechanisms underlying chemoresistance and identify new targets to improve patient outcomes. Here, we report a novel role for the ST6Gal-I sialyltransferase in gemcitabine resistance. Utilizing MiaPaCa-2 and BxPC-3 PDAC cells, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 50 publications
3
62
0
Order By: Relevance
“…However, α2,6-hypersialylation of fibronectin receptor integrin α5β1 could avoid anoikis by preventing galectin-1 binding to integrins [91,92]. On the other hand, α2,6-sialylation showed vital effects on therapeutic resistance in many cancers [93][94][95], possibly through the sialylated receptors such as EGFR [96][97][98]. EGFR sialylation was reported to suppress its dimerization and to induce phosphorylation, reducing the effects of tyrosine kinase inhibitors [98].…”
Section: Sialic Acids Assist To Resist Apoptosis and Cancer Therapymentioning
confidence: 99%
“…However, α2,6-hypersialylation of fibronectin receptor integrin α5β1 could avoid anoikis by preventing galectin-1 binding to integrins [91,92]. On the other hand, α2,6-sialylation showed vital effects on therapeutic resistance in many cancers [93][94][95], possibly through the sialylated receptors such as EGFR [96][97][98]. EGFR sialylation was reported to suppress its dimerization and to induce phosphorylation, reducing the effects of tyrosine kinase inhibitors [98].…”
Section: Sialic Acids Assist To Resist Apoptosis and Cancer Therapymentioning
confidence: 99%
“…Previous studies by our group have demonstrated that exposure of cells to cytotoxic stimuli or cell stressors exerts selective pressure, leading to the expansion of clonal variants with high ST6Gal-I expression (18,19,23,24,36,37). To determine whether this was true in the context of hypoxia, we cultured parental MiaPaCa-2 cells in a hypoxia chamber for 6 weeks to generate a population capable of proliferating under chronic hypoxia ("hypoxia-adapted").…”
Section: St6gal-i Activity Provides a Proliferative Advantage In Hypomentioning
confidence: 99%
“…After the overnight incubation, one set of plates was stained with crystal violet to obtain a baseline value for cell number. The remaining plates were placed into hypoxic culture (0.5% O 2 ) for 24, 48, or 72 h. Subsequently, cells were fixed with 4% paraformaldehyde and then stained with a 0.5% (w/v) crystal violet solution (24). To quantify cell number, the crystal violet-stained cultures were solubilized using a 10% acetic acid solution, and solution absorbance was measured on a Biotek plate reader at 590 nm.…”
Section: Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…ST6Gal-I regulates tumor cell phenotype by modulating the sialylation, and therefore function, of key receptors that drive malignant cell behaviors [11][12][13][14][15][16][17]. We and others have shown that ST6Gal-I activity confers all of the hallmark features of a CSC including increased expression of canonical CSC markers [18], invasive potential [16,19], tumor-initiating potential [9,20], and resistance to hypoxia, chemotherapeutics, and radiation [14,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%